Oxidative stress parameters in blood and urine of metal-shelf factory workers - (:unkn) unknown (My University, 2013)
Amaç: Bu çalışmada, fabrika ortamında çalışan işçilerin antioksidan seviyeleri (glutatyon, glutatyon redüktaz, glutatyon peroksidaz, glutatyon transferaz, katalaz ve süperoksit dismutaz), lipit peroksidasyon ürünleri (plazma, eritrosit ve idrarda malondialdehit) ve DNA hasar ürünü 8-hidroksideoksiguanozin (8-OH-2-dG) ölçülerek işçilerdeki oksidatif stres düzeylerinin karşılaştırılması amaçlanmıştır. Yöntem: Çalışmaya İstanbul sanayi bölgesinde metal raf üretimi yapan bir fabrikanın üretim kısmında çalışan 24 işçi ile 16 kişiden oluşan bir kontrol grubu alınmış, hastalardan ve kontrol gruplarından alınan kan ve idrar örneklerinde oksidatif stres parametreleri incelenmiştir. Bulgular: İşçilerde glutatyon transferaz, katalaz, süperoksit dismutaz ve plazma, idrar ve eritrosit malondialdehit düzeyleri kontrol grubuna göre yüksek bulunurken, glutatyon peroksidaz ve glutatyon düzeyleri düşük bulunmuştur. Glutatyon redüktaz ve 8-OH-2-dG değerleri kontrol grubuna göre sırasıyla düşük ve yüksek bulunmuş olmakla birlikte değerler arasındaki fark istatistiksel olarak anlamlı değildir. Sonuç: Metal raf üretim fabrikasında çalışan işçiler kontrol grubuna göre serbest radikallerin zararlı etkilerine daha fazla maruz kalmaktadır.

Objectives: We have investigated the level of antioxidants (glutathione (GSH), GSH-reductase, GSH-peroxidase, GSHtransferase, catalase (CAT) and superoxide dismutase (SOD)), lipid peroxidation products (plasma, erythrocyte and urinary malondialdehyde (MDA)) and urinary DNA damage product 8-hydroxydeoxyguanosine (8-OH-2 -dG) in metal-shelf factory workers and compared the levels to those of a control group working in a different work area. Methods: Twenty four workers working in a metal shelf production factory and sixteen apparently healthy male volunteers without environmental and work place exposure were included in the study. Blood and urine samples were examined for oxidative stress parameters. Measurement of 8-OH-2 -dG was by high performance liquid chromatography (HPLC), while other parameters were measured by colorimetric methods. Results: GSH-transferase, CAT, SOD activities and plasma, erythrocyte and urinary MDA levels of metal shelf production factory workers were higher than for the control group, whereas, GSH-peroxidase and GSH in workers were lower than for controls. Moreover, while GSH-reductase activity was lower, 8-OH-2 -dG level was higher than the control group but the difference was not statistically significant. Conclusion: As a result of increased industrialization, air pollution and hazardous working conditions there is a deterioration of the balance between oxidant and antioxidant levels which affects the structure of macromolecules such as DNA, lipids and proteins.
Metal raf üretim fabrikasında çalışan işçilerde kan ve idrar oksidatif stres parametreleri
Keywords: Genel ve Dahili Tıp